Is it Friday yet? Mothers talking about sex online - Sarah Pedersen (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2014)
Inspired by the media furore over ‘penis beaker gate’ (October 2013), this article investigates the discussion of sex on the UK parenting website Mumsnet. It asks why there was such shock at finding mothers discussing sexual matters online, what types of discussion related to sex can actually be found on Mumsnet and why women use Mumsnet to discuss these matters. It suggests that the Internet in general offers a new place for women to discuss and discover their sexuality and that Mumsnet in particular offers an interactive and anonymous forum for women whose needs in this area are not met by the mainstream media. On Mumsnet women seek advice and support from others in similar situations, attempt to establish ‘norms’ relating to sexual behaviour, and supplement information given by health professionals.